The Egyptian Community Culture in Nawal El-Sa’dawi’s Perempuan Di Titik Nol Novel: A Literary Anthropological Study - Selly Marita (Alphabet: A Biannual Academic Journal on Language, Literary, and Cultural Studies, 2021)
This study aimed to reveal the Egyptian community culture portrayed in Nawal El-Sa’dawi’s Perempuan di Titik Nol novel. The method used in this study was descriptive qualitative with a literary anthropological approach. The data in this study were taken from the Perempuan di Titik Nol novel, while the data were the events experienced by Firdaus as the main character in the novel. This paper found out some of the customs of Egyptian community in the PdTN novel as a cultural representation of Egyptian society. The results of this study showed four cultures of the Egyptian community, including: 1) matchmaking culture, as an effort to obtain material benefits from the matchmaking; 2) patriarchal culture that considers men as subjects who have power while women as objects whose roles are marginalized; 3) materialist culture, seeing things based on world treasures; and finally, 4) bribery culture, both by using either money or women’s bodies.